When Overweight Is the Normal Weight: An Examination of Obesity Using a Social Media Internet Database - Kuebler, Meghan; Yom-Tov, Elad; Pelleg, Dan; Puhl, Rebecca M; Muennig, Peter (PLoS One, 2013)
Using a large social media database, Yahoo Answers, we explored postings to an online forum in which posters asked whether their height and weight qualify themselves as “skinny,” “thin,” “fat,” or “obese” over time and across forum topics. We used these data to better understand whether a higher-than-average body mass index (BMI) in one’s county might, in some ways, be protective for one’s mental and physical health. For instance, we explored whether higher proportions of obese people in one’s county predicts lower levels of bullying or “am I fat?” questions from those with a normal BMI relative to his/her actual BMI. Most women asking whether they were themselves fat/obese were not actually fat/obese. Both men and women who were actually overweight/obese were significantly more likely in the future to ask for advice about bullying than thinner individuals. Moreover, as mean county-level BMI increased, bullying decreased and then increased again (in a U-shape curve). Regardless of where they lived, posters who asked “am I fat?” who had a BMI in the healthy range were more likely than other posters to subsequently post on health problems, but the proportions of such posters also declined greatly as county-level BMI increased. Our findings suggest that obese people residing in counties with higher levels of BMI may have better physical and mental health than obese people living in counties with lower levels of BMI by some measures, but these improvements are modest.